Instagram Social Media Management Strategy to Enhance Institutional Image: A Case Study of KP2KP Bintuhan's @pajakbintuhan Account - Saputra, Tri Anjar; Octaviani, Vethy; SM, Anis Endang (Universitas Dehasen Bengkulu, 2025)
This study aims to describe the Instagram social media management strategy used to enhance the institutional image of KP2KP Bintuhan through the @pajakbintuhan account. Employing a qualitative descriptive approach, data were collected through interviews with three key informants and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the Instagram management strategy follows Luttrell's Circular Model of Social Media (SoMe) (2019), consisting of four stages: (1) Share, focusing on participation, connection, and trust-building; (2) Optimize, by listening to and learning from public feedback and engaging in authentic communication; (3) Manage, through media monitoring, real-time interaction, and quick responses to audience comments; and (4) Engage, involving internal and external stakeholders such as the head office in disseminating public information. This strategic approach has proven effective in enhancing the institution’s positive image in the public eye.